Favoriser le bien-être de l'apprenant : une question de sublimation ? - Pascaline Tissot
Based on the analysis of mediated discussion groups conducted with pupils in a primary school operating in cooperative classes and with secondary school pupils in a more traditional establishment, this text draws on psychoanalysis to put into perspective the pupils' feelings on the notion of well-being and the teacher's position. Understood as a condition for the emancipation of the subject, well-being is approached from the angle of the relationship to knowledge in the transmission link. How can teacher support the pupil in his or her learning process so that the desire for knowledge is transformed into intellectual curiosity? If, for Freud, this path of sublimation is one of the dimensions of the educational process, wouldn't well-being in transmission be sought in teacher's ability to facilitate this sublimatory activity?